Electromagnetic Waves Propagation in Complex Matter - Kishk, Ahmed (IntechOpen, 2011)
This volume is based on the contributions of several authors in electromagnetic waves propagations. Several issues are considered. The contents of most of the chapters are highlighting non classic presentation of wave propagation and interaction with matters. This volume bridges the gap between physics and engineering in these issues. Each chapter keeps the author notation that the reader should be aware of as he reads from chapter to the other.